The trend of dog rabies with vaccination using seir model case study: Bolgatanga district, Ghana, This paper has been withdrawn. - Donkoh, Elvis; Kabo-bah, Kamila; Asiedu, Seth (International Journal of Applied Mathematical Research, 2014)
This paper has been withdrawn.